PENGUATAN TECHNOPRENEUR MUDA MELALUI EDUKASI TECHNOPRENEURSHIP DAN KEUANGAN - Hilyah Magdalena; Syafrul Irawadi; Ade Septryanti; Eza Budi Perkasa (Jurnal Pengabdian Masyarakat Nasional, 2026)
The demographic bonus of 2030 demands that the younger generation be prepared not only as job seekers but also as technology-based job creators (technopreneurs) who are proficient in financial management. This community service activity aimed to enhance the understanding of technopreneurship and financial literacy among ISB Atma Luhur Pangkalpinang students through an integrated public lecture and training. The method used was participatory with an andragogical approach, implemented in three stages: preparation, implementation, and evaluation. The activity was attended by 188 participants from various educational institutions in the Bangka Belitung Islands Province. Evaluation results showed a significant increase in understanding by 47.0 percent (from a pre-test score of 54.7 to a post-test score of 80.4), with the highest increase in the financial literacy domain (53.5 percent) compared to technopreneurship (41.2 percent). Indicators with the highest improvement included the concept of the hedonic treadmill (44.0 points), investment risk profile (40.0 points), as well as the PKW program and understanding of stocks (36.0 points each). Participant satisfaction levels were very high with an average of 4.64 on a scale of 5. The activity also successfully stimulated the birth of 25 technology-based business ideas and identified 45 participants in need of further assistance. The integration of technopreneurship and financial literacy proved effective in equipping the younger generation with a holistic understanding of technology-based entrepreneurship and wise financial management, making a real contribution to optimizing the 2030 demographic bonus and achieving national entrepreneurship ratio targets.